Structure of 2'-Deoxymugineic Acid, A Novel Amino Acid Possessing an Iron-Chelating Activity - Kyosuke Nomoto; Himeko Yoshioka; Masazumi Arima; Shinji Fushiya; Sei'ichi Takagi; Tsunematsu Takemoto (CHIMIA)
A novel amino acid possessing an iron-chelating activity, 2'-deoxymugineic acid, has been isolated from root washings of water-cultured wheat (Triticum aestivum L.) under iron deficient media, and shown to have structure (1) by chemical and physicochemical studies.